Large deformation and failure analysis of the corrugated flexible composite skin for morphing wing. (1st March 2023) - Liu, Tian-Wei; Bai, Jiang-Bo; Li, Shao-Lin; Fantuzzi, Nicholas
Highlights: Based on equilibrium equations, classical laminate theory and maximum stress criterion, the analytical model for predicting the tensile behaviour of the Flexible Composite Skin (FCS) was established. The FEM was established to predict the tensile behaviour of the FCS. The maximum stress criterion is used to predict the tensile failure load and failure mode of the FCS during the tensile deformation process. The prediction results of the analytical model and FEM were compared with experimental results. The analytical model and FEM show good prediction accuracy for predicting the complete tensile load–displacement curve, tensile failure load and tensile failure mode of the FCS. Abstract: The morphing wing has been a research hotspot in the aviation field in recent years, and the flexible skin is one of the most important parts of the morphing wing. The analytical method, experimental method and numerical simulation were employed in this paper to evaluate the tensile behaviour and functional mechanisms of a new corrugated Flexible Composite Skin (FCS). The FCS is composed of two thin-walled curved Fibre-Reinforced-Plastics (FRP) composite shells which can be extended and contracted through pure elastic deformation during the large deformation process. Based on equilibrium equations, classical laminate theory and the maximum stress criterion, the analytical model for predicting the tensile behaviour of the FCS was established. FCS specimens were fabricated using vacuum bag method. Tensile experiments of FCS specimens were performed, and complete tensile load–displacement curves and tensile failure loads were measured. In addition, a Finite Element Model (FEM) was established to predict the tensile behaviour of the FCS. Prediction results using the analytical model and the FEM were compared with experimental results, and the three were in good agreement. Finally, the effect of geometric parameters (i.e. radius of curvature, center angle and thickness) on the tensile behaviour of the FCS was further investigated with the aid of the analytical model. It is shown that geometric parameters are one of the key factors affecting the tensile behaviour of the FCS.